Accelerating Kaluza-Klein Universe In Modified Theory Of Gravitation - Katore, S. D.; Hatkar, S. P.; Tadas, D. P. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The purpose of this paper is to study the Kaluza-Klein universe in the context of the f (R, T) gravity theory using magnetized strange quark matter (MSQM). To obtain exact solutions of field equations, we assume two types of volumetric expansion: power law and exponential law volumetric expansions. The violation of energy conditions has been studied. The physical and geometrical properties of the examined model have also been investigated thoroughly. Целью данной статьи является изучение Вселенной Калуцы- Клейна в контексте f (R, T) теории гравитации с использованием намагниченного странного кваркового вещества (MSQM). Точные решения уравнений поля получены для двух типов объемного расширения: степенного и экспоненциального. Изучено нарушение энергетических условий. Подробно исследованы также физические и геометрические свойства рассматриваемой модели.
Keywords: Astrophysics